Gouverneur Morris and the American Revolution, - Mintz, Max M. (University of Oklahoma Press, 1970)
Report for Bachelor of Engineering (Naval Architecture)., ***CD-ROM held at loans desk***
Keywords: 1775-1783; New York (State); 1775-1783; United States; Biography; Legislators; Biography; United States; Foreign relations; History; Morris; Gouverneur; 1752-1816; Statesmen; Politics and government; Revolution; 1775-1783; dept.his; faculty_collection

Lyautey in Morocco: Protectorate Administration, 1912-1925 - Scham, Alan (University of California Press, 1970)
Keywords: Lyautey; Louis Hubert Gonzalve; 1854-1934; Morocco; Politics and government; dept.his; faculty_collection